CAT tools in translation of collocations: An empirical study of impact on Saudi Electronic University learners - Alowedi, Noha Abdullah (Linguistics and Culture Review, 2021)
This study aims to fill this gap by exploring the impact of CAT tools on translation and the complications that occur during collocation translation. The study used a collocation test of ten statements to be responded to by 95 students of Saudi Electronic University. The data was analyzed to investigate the productivity of the respondents using CAT tools for translation of the collocations in the assessment. Findings showed a positive impact of these tools on the student’s performances with an average score of 71.97% in the collocation test. Results also showed that there were no significant differences between students’ score in the test attributable to their level of enrolment. Finally, no statistical differences were found between students’ score in selecting the correct verb collocation and selecting the appropriate rendering. The study concludes with reinforcing the importance of multiple ways of training translation students in the use of CAT Tools and recommends providing students with access to these. Furthermore, the study also recommends pertinent solutions to the problems likely to arise in the integration of CAT tools in translation studies